Pengaruh Penerapan Metode Bernyanyi Terhadap Peningkatan Hafalan Mufrodat Kitab Amtsilatut-Tashrifiyah - Khalilurrahman; Mustadi Mustadi; Ainul Halim (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
Memorizing the mufrodat in the book amtsilatut-tasrifiyah is important for students of Madrasah Mu`allimin Mu`allimat Sunan Drajat East Java because it is also the basis for being able to read salaf books. Shorof learning in Class IV D Madrasah Mu`allimin Mu`allimat Sunan Drajat is quite effective, but students tend to be less enthusiastic in implementing the learning. This type of research is quantitative research. The population in this study were students of Madrasah Mu`allimin Mu`allimat Sunan Drajat and the sample used was class IV D of Madrasah Mu`allimin Mu`allimat Sunan Drajat, East Java. The instruments used are: Tests, Interviews, and Documentation. To strengthen the results of the research carried out, the researchers analyzed the data using the t-test formula.